Refining use of chemigated rimsulfuron for branched broomrape management in California processing tomato - Matthew Fatino; Bradley D. Hanson (Weed Technology, 2025)
Branched broomrape management is of increasing concern to California processing tomato growers. Field research was conducted in 2023 and 2024 to evaluate various application timings of chemigated rimsulfuron alone, preplant-incorporated (PPI) sulfosulfuron paired with chemigated rimsulfuron, and foliar maleic hydrazide alone and paired with PPI sulfosulfuron and chemigated rimsulfuron. In 2023, all treatments with 70 g ai ha−1 rimsulfuron, alone or paired with PPI sulfosulfuron, reduced broomrape emergence 77% to 92% compared to the nontreated control. In 2024, broomrape pressure was higher, and all rimsulfuron treatments reduced broomrape emergence 68% to 86% compared to the control. In both years, five applications of foliar maleic hydrazide reduced broomrape emergence through at least mid-season. The 2024 experiment included a combination treatment of PPI sulfosulfuron, chemigated rimsulfuron, and foliar maleic hydrazide, which resulted in <4 broomrape clusters plot−1. In a 2024 grower-scale demonstration trial, two application regimes totaling 70 g ai ha−1 of chemigated rimsulfuron reduced broomrape emergence 83% to 89% compared to the control. Overall, chemigated rimsulfuron applied at various timings and rates totaling 70 g ai ha−1 reduced broomrape emergence by two-thirds or more compared to the nontreated plots. No crop injury was observed in trials with rimsulfuron, sulfosulfuron, or maleic hydrazide treatments in small-plot trials or with rimsulfuron in the grower-scale demonstration trial. Under a recently approved 24(c) Special Local Need label, California growers can use three applications of rimsulfuron applied via chemigation to suppress broomrape in known infested fields or to reduce the risk of broomrape establishment in fields of concern for this quarantine pest. Promising results from sulfosulfuron and maleic hydrazide suggest that registering additional herbicides could help develop even more robust branched broomrape management programs.